2017
DOI: 10.1155/2017/4691389
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Neutrophil Gelatinase-Associated Lipocalin Is Complementary to Albuminuria in Diagnosis of Early-Stage Diabetic Kidney Disease in Type 2 Diabetes

Abstract: Background Two clinical phenotypes of diabetic kidney disease (DKD) have been reported, that is, with or without increased albuminuria. The aim of study was to assess the usefulness of urinary neutrophil gelatinase-associated lipocalin (uNGAL) for the early diagnosis of DKD in the type 2 diabetes mellitus (T2DM). Methods The study group consisted of 123 patients with T2DM (mean age 62 ± 14 years), with urine albumin/creatinine ratio (uACR) < 300 mg/g and eGFR ≥ 60 ml/min/1.73 m2. The control group included 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…In this study, serum LCN2 levels were shown to be higher in the T2DM group than in the NGT group, consistent with previous reports [12,19]. Since BMI and sex have been shown to be related to serum LCN2 levels in human, the subjects in the NGT group who had no statistical differences in those parameters compared to T2DM group were chosen as controls in this study [14,20].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, serum LCN2 levels were shown to be higher in the T2DM group than in the NGT group, consistent with previous reports [12,19]. Since BMI and sex have been shown to be related to serum LCN2 levels in human, the subjects in the NGT group who had no statistical differences in those parameters compared to T2DM group were chosen as controls in this study [14,20].…”
Section: Discussionsupporting
confidence: 88%
“…Nauta et al [ 32 ] observed higher concentrations of urine NGAL and KIM-1 in normoalbuminuric diabetic patients comparing to healthy subjects. Also, we have previously reported increased urine NGAL concentrations among patients with early stages or risk for DKD [ 33 ], similarly to other groups [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 79%
“…It is a low molecular weight protein associated with human neutrophil gelatinase, whose urine assay is considered a useful indicator of the course of acute kidney injury in the prerenal mechanism [11]. The appearance of this protein in the urine of patients in the early stages of CKD, gives useful diagnostic information as to the sites and degree of injury to the renal interstitium [12]. In patients with CHF, increased uNGAL may be a marker of tubulo-interstitial injury and is associated with an increased risk of worsening renal function, increased hospitalization and overall mortality [33].…”
Section: Discussionmentioning
confidence: 99%
“…The following low molecular weight proteins, freely ltering through the glomeruli and mostly reabsorbed in the proximal tubule of the nephron, were considered indicators of glomerular renal assessment: cystatin C in urine (uCysC) and serum (sCysC) and lipocalin-type serum prostaglandin D2-synthase (sPGD2S) [9,10]. We chose urinary lipocalin associated with neutrophil gelatinase (uNGAL) secreted mainly from the distal nephron tubules in response to a nephrotoxic agent or ischemia as biomarker in the assessment of renal tubules [11,12].…”
Section: Introductionmentioning
confidence: 99%